Motivated reasoning and climate change. (December 2021) - Bayes, Robin; Druckman, James N
Highlights: Opinions about climate change have polarized based on partisan orientation. A preeminent explanation for climate change attitude polarization is directional motivated reasoning. Recent work challenges this account, suggesting polarization is consistent with individuals forming opinions with the goal of accuracy. Future work would benefit from careful attention to individuals' motivations. Abstract : Despite a strong scientific consensus, there remains a substantial partisan divide in the U.S. regarding belief in, and attitudes toward, human-caused climate change. A preeminent explanation of this phenomenon is directional 'motivated reasoning', in which new information is processed in service of reaching a pre-determined, desired conclusion. Much existing work theorizes that partisan polarization occurs because members of the two political parties are assimilating new information to fulfill different desired conclusions, rooted in different party norms, values, or prior standing beliefs. However, recent work challenges this account. The next generation of work on motivated reasoning and climate change beliefs must address these challenges by distinguishing between distinct motivations that may drive motivated reasoning—most significantly, by identifying when partisans are truly striving to reach a desired conclusion and when they are striving to be accurate.